1998
DOI: 10.1038/sj.onc.1201921
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recruitment of p120RasGAP and its associated protein, p190RhoGAP, to the cytoskeleton during integrin mediated cell-substrate interaction

Abstract: The interaction of cells with their substrate triggers cascades of signal transduction that result in profound changes in cell morphology. The nature of these signals and how they are integrated to orchestrate changes in cell shape are beginning to be elucidated. In particular, adhesive interactions between cells and their substrate, mediated by cell-surface integrins and extracellular matrix (ECM) proteins, appear to result in massive rearrangement of the cell cytoskeleton via the small Gprotein, Rho. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Similarly, Sydor et al [43] have shown that the Raf -Ras complex has an extremely short lifetime, after which Raf is released for downstream signalling. The resulting Ras species, denoted RasGTP Ã , is no longer capable of activating Raf and will undergo GTP hydrolysis catalysed by GTpase activating proteins (GAPs), which are recruited to focal adhesions after integrin-ligand binding [44,45]. In the case of high [Raf], Ras accumulates as RasGTP Ã , suggesting that the RafRasGTP reaction is much faster than the action of GAPs in recycling Ras.…”
Section: Ras and Raf As Regulators Of Erk Activitymentioning
confidence: 99%
“…Similarly, Sydor et al [43] have shown that the Raf -Ras complex has an extremely short lifetime, after which Raf is released for downstream signalling. The resulting Ras species, denoted RasGTP Ã , is no longer capable of activating Raf and will undergo GTP hydrolysis catalysed by GTpase activating proteins (GAPs), which are recruited to focal adhesions after integrin-ligand binding [44,45]. In the case of high [Raf], Ras accumulates as RasGTP Ã , suggesting that the RafRasGTP reaction is much faster than the action of GAPs in recycling Ras.…”
Section: Ras and Raf As Regulators Of Erk Activitymentioning
confidence: 99%
“…We found that expression of oncogenic Ras in LTR-H-Ras(A) cells induced the translocation of p190 Rho-GAP from the cytosol to a detergent-insoluble cytoskeletal fraction. Similarly, integrinmediated cell-substrate interaction has been shown to result in p190 Rho-GAP recruitment to the cytoskeleton at 1-2 h after plating NIH 3T3 cells on fibronectin, and this change in subcellular localization of Rho-GAP occurs at a time when Rho⅐GTP levels are elevated (11,36,44). In contrast to the stimulation of RhoA activity by prolonged integrin engagement, early integrin signaling within 10 -15 min after plating cells on fibronectin induces Src-dependent tyrosine phosphorylation of p190 Rho-GAP, increases Rho-GAP activity, and transiently inactivates RhoA (64).…”
Section: Effect Of Oncogenic Ras On the Interaction Of P190 Rho-gap Wmentioning
confidence: 99%
“…7c, Membrane). To determine whether the decrease in cytosolic Rho-GAP may be the result of a shift into a cytoskeletal compartment, we extracted cells in Triton X-100-containing lysis buffer and examined the detergent-insoluble cytoskeletal fraction (44). Dexamethasone treatment of LTR-H-Ras(A) cells, but not of wild type NIH 3T3 cells, induced a significant increase in the amount of p190 Rho-GAP associated with the Triton-insoluble cytoskeletal fraction (Fig.…”
Section: Rho Activation In Nih 3t3 Ltr-h-ras(a) Cells and Nih 3t3 Celmentioning
confidence: 99%
See 1 more Smart Citation
“…This function likely depends on the need to regulate the balance between cell-cell and cell-substratum interactions controlled by p120-Catenin, which can also regulate morphogenesis. Since p190RhoGAP directly interacts with focal adhesion kinase, regulates both RhoA activity and other multiple signaling pathways related to cell cycle [42], differentiation [13,14], morphogenesis [43], and determines cell shape [31,44], motility [45], and cell-cell interaction [41,46], it acts as an important conduit of information from the extracellular mechanical world [47] and a key decision maker in determining the coordinated control of temporally regulated phenotypic outcome.…”
Section: The Critical Role Of P190rhogap In Cardiac Endothelial Cell mentioning
confidence: 99%